Double-Outlet Right Atrium: Review of a Rare Anomaly With an Exemplary Case. Issue 1 (January 2020) - Ambra, Miette; Nuri, Halkawt Ali; Giuseppe, Pomé; Marasini, Maurizio; Francesco, Santini
Background: Double-outlet right atrium (DORA) is a rare congenital cardiac defect, where the right atrium (RA) is connected to both the right ventricle (RV) and the left ventricle (LV). Double-outlet right atrium is classified into two types, each containing two subtypes: malaligned atrial septum with common or single atrioventricular (AV) valve and malaligned ventricular septum (VS) with adequate or inadequate RV. The VS type is characterized by straddling right AV valve (RAVV) with intact VS, resulting in two RAVV orifices. Methods: We report a case of "acquired DORA" in a 17-year-old male patient previously treated with subaortic VSD closure. At admission, we diagnosed DORA with VS malalignment and adequate RV. The patient had 2 orifices within the RAVV, connecting the RA to both the RV (via RAVV orifice 1) and the LV (via RAVV orifice 2). The latter was insufficient, with severe LV to RA shunt. A review of the literature indexed in PubMed and Scopus databases was undertaken. Results: The patient underwent biventricular repair through closure of the RAVV orifice 2 with a pericardial patch. Pacemaker implantation for complete AV block was necessary. Postoperative course and follow-up were regular. The literature review showed 39 cases of DORA, of which 8 had a malaligned VS and an adequate RV, as in our case. Conclusion: Acquired DORA is an interesting post-surgical variant of a rare congenital heart defect. Biventricular repair is a feasible and viable option, which involves closing the third AV orifice. Careful attention is required in order to avoid injury to the conduction system.